1996
DOI: 10.1079/bjn19960072
|View full text |Cite
|
Sign up to set email alerts
|

Body composition in female anorexia nervosa patients

Abstract: For the first time, body composition has been studied in a very large sample of female anorexia nervosa patients (n 200) using two methods: anthropometry (skinfold thickness) and densitometry (underwater weighing). The concurrent validity of both methods appeared to be good (v 0.84). Although the mean percentage of body fat (13.5) in our sample corresponds with most of the previous reports, the range (4.3-24.8) is great. Our study shows that BMI is not a good measure of fatness. Age and duration of illness wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
27
2
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 52 publications
7
27
2
2
Order By: Relevance
“…Striking changes in body composition can be observed in patients with anorexia nervosa: for instance, in our study the initial body weight corresponded on average to 73% of controls' value while (according to DXA) FFM and FM were reduced by 17 and 71%, respectively. This is in agreement with previous papers which have indicated that in this case the reduction in body mass involves both adipose and lean tissues, but the former to a greater extent (Fohlin, 1977;Davies et al, 1978;Forbes et al, 1984;Probst et al, 1996;Orphanidou et al, 1997;Polito et al, 1998).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Striking changes in body composition can be observed in patients with anorexia nervosa: for instance, in our study the initial body weight corresponded on average to 73% of controls' value while (according to DXA) FFM and FM were reduced by 17 and 71%, respectively. This is in agreement with previous papers which have indicated that in this case the reduction in body mass involves both adipose and lean tissues, but the former to a greater extent (Fohlin, 1977;Davies et al, 1978;Forbes et al, 1984;Probst et al, 1996;Orphanidou et al, 1997;Polito et al, 1998).…”
Section: Discussionsupporting
confidence: 82%
“…Several investigators have evaluated body composition in anorectic patients (Fohlin, 1977;Hannan et al, 1990;Krahn et al, 1993;Scalfi et al, 1993;Nuñiez et al, 1994;Probst et al, 1996;Orphanidou et al, 1997;Polito et al, 1998): a decrease of both fat-free mass (FFM) and fat mass (FM) has always been reported, with lean tissues accounting for a variable percentage of the reduction in body mass. With respect to refed patients, changes in FFM and FM (Orphanidou et al, 1997;Probst et al, 2001), body potassium (Pirke et al, 1986), total body water and its intracellular=extracellular distribution (Vaisman et al, 1988), as well as in bioimpedance analysis (Polito et al, 1998;Scalfi et al, 1999), have been observed after weight recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Fat mass-related parameters (TSF, SSF and AFA) appeared clustered under the 10th percentile (100%, 79%, 93% of the patients, respectively), while MAC, which is considered a better marker of muscle mass than fat mass, AMC and AMA were found in 43, 64 and 64% of the patients, respectively, above the 10th percentile (Frisancho, 1981). Several authors have also found a greater impairment of fat mass than muscle mass in undernourished AN patients (Russell et al, 1983;Forbes et al, 1984;Melchior et al, 1989;Krahn et al, 1993;Probst et al, 1996;Polito et al, 1998). Beaumont et al, (1993) suggest that a relatively high protein diet, together with the high physical activity levels that are characteristics of the illness, both features found in the patients of this study, will play a nitrogen-sparing role, which will explain initial weight loss being due almost entirely to loss of adipose tissue.…”
Section: Discussionmentioning
confidence: 96%
“…The limitations of BMI alone become apparent, for example, when trying to predict resumption of menses (Sobanski et al, 1997;Falk & Halmi, 1982). Studies in adults, using more complex body composition models than BMI, have attempted to tease out the relationship between FM and normal endocrine function (Birmingham et al, 1996;Mazess et al, 1990;Probst et al, 1996;Vaisman et al, 1988;Zamboni et al, 1997). However, recent evidence suggests that FFM may be as or more important than fatness in the development of osteoporosis in AN (Grinspoon et al, 1999).…”
Section: Introductionmentioning
confidence: 99%